Development of 21st Century Skill-Based Muthola'ah Teaching Materials - Abdul Kosim; Novy Maryani (AL-TA'RIB : Jurnal Ilmiah Program Studi Pendidikan Bahasa Arab IAIN Palangka Raya, 2025)
In this modern era, there are many challenges in implementing Arabic language learning, particularly in Arabic text literacy activities. Literacy is not just about reading but also understanding what is read, both from a grammatical and content perspective. In Arabic itself, to train literacy, there is the Muthala'ah learning method. Muthala'ah learning not only focuses on teaching the proper reading of Arabic texts but is also accompanied by the exploration of morphology, syntax, and the meaning of the text being read. Therefore, to make Muthala'ah learning relevant and engaging for today’s time, this study aims to describe the development of Muthala'ah teaching materials based on 21st-century skills. The method used in this research is Design-Based Research (DBR) with descriptive data analysis. The results of this study include examples of Muthala'ah texts that are based on 21st-century skills, which include communicative, creative, collaborative, and critical thinking indicators. The presentation of the texts is also accompanied by visuals relevant to the text and explanations of several vocabulary words considered difficult. The findings highlight the importance of integrating 21st-century skills in Muthala'ah teaching, enhancing engagement, comprehension, and critical thinking, while visuals and vocabulary support improve accessibility and learning effectiveness.